The Implementation of the Merdeka Belajar Curriculum and Its Impact on Students’ Motivation in Learning English at MAN Palopo - Annisa Gita Mulyani; Rustan Santaria; Jufriadi Jufriadi (Faculty of Education and Teacher Training of UIN Palopo, 2026)
This research investigates the impact of the Merdeka Belajar Curriculum on students’ motivation to learn English at MAN Palopo. As a newly introduced educational approach in Indonesia, the Merdeka Belajar Curriculum emphasizes student-centered learning, autonomy, and the development of individual interests and competencies. The study adopts a qualitative descriptive method, using observations, interviews, and documentation to gather data from English teachers and 11th-grade students involved in the curriculum implementation. Findings reveal that the curriculum has significantly influenced students’ motivation in learning English. Many students reported feeling more engaged, confident, and enthusiastic in participating in English learning activities. They also showed improvements in both their spoken and written English skills. Despite these positive outcomes, the implementation process faces several challenges, including inadequate school facilities, limited teacher preparedness, and a lack of ongoing professional development. Nonetheless, when implemented effectively, the Merdeka Belajar Curriculum has the potential to enhance students’ intrinsic motivation and foster a more meaningful English learning experience.